2022
DOI: 10.3389/fmicb.2022.1041338
|View full text |Cite
|
Sign up to set email alerts
|

The protective immunity induced by intranasally inoculated serotype 63 chimpanzee adenovirus vector expressing human respiratory syncytial virus prefusion fusion glycoprotein in BALB/c mice

Abstract: Human respiratory syncytial virus (RSV) is a ubiquitous pediatric pathogen causing serious lower respiratory tract disease worldwide. No licensed vaccine is currently available. In this work, the coding gene for mDS-Dav1, the full-length and prefusion conformation RSV fusion glycoprotein (F), was designed by introducing the stabilized prefusion F (preF) mutations from DS-Cav1 into the encoding gene of wild-type RSV (wtRSV) F protein. The recombinant adenovirus encoding mDS-Cav1, rChAd63-mDS-Cav1, was construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The copyright holder for this preprint (which this version posted April 19, 2023. ; https://doi.org/10.1101/2023.04.17.537220 doi: bioRxiv preprint virus (RSV) or MERS-CoV infection (35,36,37). In this study, we utilized a novel simian adenovirus 23 6).…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint (which this version posted April 19, 2023. ; https://doi.org/10.1101/2023.04.17.537220 doi: bioRxiv preprint virus (RSV) or MERS-CoV infection (35,36,37). In this study, we utilized a novel simian adenovirus 23 6).…”
Section: Discussionmentioning
confidence: 99%
“…Two needle-free COVID-19 vaccines that are delivered through the mouth or nose have been approved for use in China and India, which are generated with adenovirus vectors by CanSino Biologics or Bharat Biotech ( 18 ). Moreover, several studies have shown the advantage of adenovirus-vectored vaccines in eliciting mucosal immunity with protective effects against respiratory virus infections such as Ebola virus, human respiratory syncytial virus (RSV), or MERS-CoV infection ( 31 33 ). In this study, we utilized a novel simian adenovirus 23 vectored COVID-19 vaccine (Sad23L-nCoV-S) with low pre-existing immunity in humans to evaluate the effects of systemic and local mucosal immunity in mice by different immunization regimens via IN and IM routes.…”
Section: Discussionmentioning
confidence: 99%